A CPW Fed Slot Antenna with Triangular Serrated Stub (International Journal of Innovative Research in Computer Science & Technology, 2022)
This paper is aimed to focus on bandwidth en hancement of a slot antenna with coplanar waveguide feeding.  The experimentation is performed on the general CPW struc ture which is having a signal conductor in the middle and two  ground layers etched on either side of feed with some gap to  allow a unique feature of uniplanar in construction. In this con text, the study of a CPW transmission line discontinuity is ap plied to prepare a slot antenna and this is followed by the study  of incorporating serrated shape in the structure.
Keywords: UWB; WPAN; W-USB